Case Report: A novel DLL4 variant in a neonate with Adams-Oliver syndrome - Huang, Yanping; Wang, Jin; Zeng, Lingkong; Wang, Shi; Zhang, Xuechen (Frontiers in Pediatrics, 2025)
Adams-Oliver syndrome is a rare congenital disorder with six subtypes that have been identified. Subtypes 1, 3, 5, and 6 have an autosomal dominant inheritance pattern, whereas subtypes 2 and 4 have an autosomal recessive inheritance pattern. The clinical phenotype of Adams–Oliver syndrome is heterogeneous and can be accompanied by abnormalities in other organs, especially the cardiovascular system, such as cutis marmorata telangiectatica congenita, pulmonary hypertension, vascular abnormalities in other organs, and congenital heart defects. Herein, we report a case of Adams–Oliver syndrome caused by a de novo variant in DLL4. The patient was a neonate with clinical manifestations of skin defects who was diagnosed with Adams–Oliver syndrome on the basis of genetic testing.